Awareness of HIV Preexposure Prophylaxis Among People at Risk for HIV: Results From the 2017–2019 National Survey of Family Growth. Issue 12 (11th December 2021) - Keddem, Shimrit; Dichter, Melissa E.; Hamilton, Alison B.; Chhatre, Sumedha; Sonalkar, Sarita
Abstract : An analysis of a national survey found that awareness of HIV preexposure prophylaxis remains low among individuals at increased risk for HIV, with only 37% being aware of preexposure prophylaxis. Abstract : Background: Although daily preexposure prophylaxis (PrEP) is now widely accepted as a safe and effective method for reducing the risk of HIV in high-risk groups, uptake has been slow. The goal of this analysis was to identify factors associated with PrEP awareness among individuals at risk for HIV. Methods: This investigation analyzed data from the Centers for Disease Control and Prevention nationally representative survey, National Survey of Family Growth, for the years 2017 to 2019. Logistic regression was used to explore the relationship between PrEP awareness and demographics, HIV risk factors, and provider HIV risk screening. Results: Only 37% of survey respondents with an increased risk of HIV were aware of PrEP. Several segments of the at-risk population had lower odds of being aware of PrEP, including heterosexual women, heterosexual men, individuals younger than 20 years, and individuals with lower levels of education. Those who participate in sex in exchange for money or drugs had significantly lower odds of being aware of PrEP. In comparison, PrEP awareness was significantly higher among nonheterosexual men and both men and women whose partners were HIV positive. Lastly, those who had been screened by a provider for HIV risk had significantly higher odds of being aware of PrEP. Conclusions: This research supports the need for policies and programs to increase awareness of PrEP, especially among certain segments of the population at increased risk for HIV.